Effects of neuromuscular training applied during Ramadan on physical fitness and injury prevention in highly-trained male youth soccer players - Belamjahad, A.; Tourny, C.; Hackney, A. C.; Laziri, F.; Saeidi, A.; El Hachimi, O.; Laher, I.; Granacher, U.; Zouhal, H. (Sports Medicine - Open, 2025)
Background The intermittent fasting period of Ramadan is associated with reductions in training volumes and intensities to maintain physical fitness levels and reduce injury occurrence. Accordingly, it might be beneficial to include neuromuscular training (NMT) applied during Ramadan to avoid detraining and promote injury prevention in soccer players. This study aimed to analyze NMT effects on physical fitness and injury prevention during the Ramadan fasting period in young soccer players.